Primary headache disorders in adolescents in North- and South-Tyrol: Findings of the EVA-Tyrol-Study. (September 2022) - Kaltseis, Katharina; Frank, Florian; Bernar, Benoît; Kiechl, Sophia; Winder, Bernhard; Kiechl-Kohlendorfer, Ursula; Knoflach, Michael; Broessner, Gregor; ,
Objective: Assessment of the prevalence of primary headache disorders, associated risk factors and use of acute/preventive medication in a representative large sample of adolescents. Methods: Within the EVA-Tyrol project, a community-based non-randomized controlled cross-sectional study, data was collected from adolescents aged 14–19 years from 45 sites across North-, East- and South Tyrol. Headaches were classified according to the latest ICHD-3 and assessed by headache specialists in face-to-face interviews. Findings: Of 1923 participants 930 (48.4%) reported having headaches. Female to male ratio was 2:1. Migraine, tension-type headache and other headache were diagnosed in 10%, 30.2% and 8.2% respectively. Medication overuse was diagnosed in 3.4%, increasing up to 21.7% in participants with chronic headache. The use of preventative medication was not reported by any adolescent. Sleep disturbances (p < 0.05), alcohol consumption (p < 0.05), low physical activity (p < 0.01) and high screen time exposure (p < 0.01) were associated with an increased risk of headaches. Conclusion: We report high prevalence of primary headache disorders and medication overuse in a large community-based sample of teenagers. Acute and preventive non-drug and pharmacological treatments are not established due to lack of paediatric headache outpatient clinics. Promoting health education in teenagers and encouraging public awareness, including that of health care providers is pivotal. Trial registration: EVA-Tyrol has been retrospectively registered at clinicaltrials.gov underhttps://clinicaltrials.gov/ct2/show/NCT03929692 since April 29, 2019.